Effects of polyethylene glycol on the structure and filtration performance of thin-film PA-Psf composite forward osmosis membranes. Issue 5 (23rd March 2016) - Wu, Yan; Zhu, Hongtao; Feng, Li; Zhang, Liqiu
ABSTRACT: In forward osmosis, internal concentration polarization is related to the properties ( e.g ., hydrophilicity, porosity, structural resistant) of membrane support layer. In this work, polyethylene glycol with a low molecular weight of 400 Da was introduced as a support layer additive during the fabrication of thin-film polyamide-polysulfone composite forward osmosis membranes. The forward osmosis performances including water flux and reverse salt flux of the membranes were tested in the mode of AL-FS where the membrane active layer faced toward feed solution. Results showed that the addition of polyethylene glycol would reduce internal concentration polarization and improve membrane performance in forward osmosis by means of enhancing membrane hydrophilicity and changing pore morphologies of membrane support layer. The membrane prepared with 6 wt.% polyethylene glycol was found to exhibit the highest water flux of 47.4 Lm −2 h −1 with a reverse salt flux of 7.6 gm −2 h −1 when using DI water and 2.0 M NaCl as the feed and the draw solution, respectively, indicating an optimal polyethylene glycol dosage of 6 wt.% in this work.